2012
DOI: 10.4238/2012.july.19.5
|View full text |Cite
|
Sign up to set email alerts
|

Selection of high heterozygosity popcorn varieties in Brazil based on SSR markers

Abstract: ABSTRACT. We analyzed genetic structure and diversity among eight populations of popcorn, using SSR loci as genetic markers. Our objectives were to select SSR loci that could be used to estimate genetic diversity within popcorn populations, and to analyze the genetic structure of promising populations with high levels of heterozygosity that could be used in breeding programs. Fifty-seven alleles (3.7 alleles per locus) were detected; the highest effective number of alleles (4.21) and the highest gene diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
3
1
Order By: Relevance
“…This result is in accordance with the observations made by Eloi et al (2012). In the literature, a deficit of heterozygotes was often encountered in maize (Yao et al, 2007;Pineda-Hidalgo et al, 2013.).…”
Section: Discussionsupporting
confidence: 82%
“…This result is in accordance with the observations made by Eloi et al (2012). In the literature, a deficit of heterozygotes was often encountered in maize (Yao et al, 2007;Pineda-Hidalgo et al, 2013.).…”
Section: Discussionsupporting
confidence: 82%
“…The Fst values indicated that Ferreira et al 89.7% of the total variation in the locus allele frequency was due to genetic differences among the lines under study (Eloi et al 2012). The genetic diversity found in this study was similar to that reported by Eloi et al (2012) and Sserumaga et al (2014). Forty percent of the loci had high PIC values (>0.6), indicating a great potential to detect differences among pure lines, confirming previous studies (Sserumaga et al 2014).…”
Section: Genetic Diversity Of Markerssupporting
confidence: 88%
“…One of the ways to estimate genetic variability in a population is to analyze the different alleles at the various gene loci with the use of molecular markers (Solomon et al, 2010). The average number of alleles obtained per locus in the present study (2.13) (Table 1) was lower than those in other studies for common corn and popcorn (Dandolini et al, 2008;Eloi, Mangolin, Scapim, Gonçalves, & Machado, 2012;Franzoni, Scapim, Beviláqua, Pacheco, & Mangolin, 2012;Trindade et al, 2010) perhaps due to the type of EST-SSR marker used, as the markers represent expressed regions of origin of common corn and not specifically for popcorn. Also, the process of repeating selection cycles in the popcorn crop prioritizes the selection of specific traits, such as grain yield and popping expansion (Franzoni et al, 2012).…”
Section: Discussioncontrasting
confidence: 71%